VARIATIONS OF SYNONYMS IN THE CULTURAL CONTEXT OF THE SCRIPTURE OF THE HARRY POTTER SERIES FILM BY J.K. ROWLING: A SEMANTIC STUDY - Gumilar, Tony Isan; Simatupang, Ervina CM (Lembaga Penelitian Universitas Pasundan, 2025)
This article purposed to: (1) identify and analyze types of synonyms based on Palmer's theory (Alexander, 2018) and (2) examine the meaning relationships contained in each type of synonym by referring to Leech's theory (Feist, 2022). This research employs a qualitative descriptive method through several stages, including watching films and reading dialogue scripts from the Harry Potter series, grouping data according to types of synonyms, analyzing data based on identified problems, and drawing conclusions from the results of the analysis. The findings reveal five types of synonyms with the following distribution: 37.2% overlapping synonyms, 25.7% stylistic synonyms, 25.7% synonyms with emotive or evaluative meaning, 5.7% collocation synonyms, and 5.7% dialect synonyms. Furthermore, based on meaning analysis, the data indicates 40% conceptual meaning, 31.6% affective meaning, 8.5% reflective meaning, 5.7% social meaning, 5.7% collocative meaning, 5.7% thematic meaning, and 2.8% connotative meaning. This study also highlights the cultural context in which these synonymous variations emerge, emphasizing how language choices in the Harry Potter series reflect British cultural nuances, social hierarchy, and magical world-building. The dialogue in the films not only serves a narrative function but also conveys deeper cultural meanings through dialectal variations, stylistic shifts, and emotive expressions, further enriching the linguistic and thematic dimensions of the story.